Azithromycin Affords Neuroprotection in Rat Undergone Transient Focal Cerebral Ischemia - Amantea, Diana; Petrelli, Francesco; Greco, Rosaria; Tassorelli, Cristina; Corasaniti, Maria Tiziana; Tonin, Paolo; Bagetta, Giacinto (Frontiers in Neuroscience, 2019)
Repurposing existing drugs represents a promising approach for successful development of acute stroke therapies. In this context, the macrolide antibiotic azithromycin has been shown to exert neuroprotection in mice due to its immunomodulatory properties. Here, we have demonstrated that acute administration of a single dose of azithromycin upon reperfusion produces a dose-dependent (ED50=1.40 mg/kg; 95% CI = 0.48-4.03) reduction of ischemic brain damage measured 22h after transient (2h) middle cerebral artery occlusion (MCAo) in adult male rats. Neuroprotection by azithromycin (150 mg/kg, i.p., upon reperfusion) was associated with a significant elevation of signal transducer and activator of transcription 3 (STAT3) phosphorylation in astrocytes and neurons of the peri-ischemic motor cortex as detected after 2 and 22 hours of reperfusion. By contrast, in the core region of the striatum, drug administration resulted in a dramatic elevation of STAT3 phosphorylation only after 22h of reperfusion, being the signal mainly ascribed to infiltrating leukocytes displaying an M2 phenotype. These early molecular events were associated with a long-lasting neuroprotection, since a single dose of azithromycin reduced brain infarct damage and neurological deficit measured up to 7 days of reperfusion. These data, together with the evidence that azithromycin was effective in a clinically relevant time-window (i.e., when administered after 4.5 h of MCAo), provide robust preclinical evidence to support the importance of developing azithromycin as an effective acute therapy for ischemic stroke.